EVALUASI PELAYANAN TROTOAR DAN STUDI PERSEPSI TERHADAP TINGKAT KENYAMANAN TROTOAR KAWASAN PERDAGANGAN - Sasmita, Dessi; Yossyafra, Yossyafra; Purnawan, Purnawan (Rang Teknik Journal, 2020)
Problems related to pedestrian pathways are often found in trades area of a city including the city of Payakumbuh, espceially in the area by the Ahmad Yani Street where as this street connect 2 main markets namely the Central Market of Payakumbuh city and the Ibuh market. Which is why this research need to be conducted, so that people can evaluate the level of Ahmad Yani streetâ€™s sidewalk service based on the level of service (LOS) value using the HCM 2000 method, the service standards are based on the Minister of Public Works Regulation Number : 03/PRT/M/2014. In addition, a pedestrian perception survey was carried out by the use of a questioner survey using the percentage interval analysis and regression analysis. Based on the analysis, the level of service from the west side of Ahmad Yani streetâ€™s sidewalk is categorized as â€œAâ€ and as for the east side is categorized as â€œBâ€. The percentage of comfort level from Ahmad Yani Streetâ€™s sidewalk of Payakumbuh city is 41,85%, which is categorized as inconvenience. The result of regression analysis indicate that the variable that affect the level of comfort from Ahmad Yani streetâ€™s sidewalk are accessibility variables with a regression coefficient of 0.644; surface conditions variable with a regression coefficient of 0.384; sanitation variable with a regression coefficient of 0.672; aesthetics variable with regression coefficient of 0.743; and sidewalk obstacle/hindrance variables with regression coefficient of -0.240. The five variables are proved to significantly affect the level of comfort from Ahmad Yani streetâ€™s sidewalk. The variation of the level of comfort from Ahmad Yani streetâ€™s sidewalk of Payakumbuh city is 47,06% influenced by those five factors as shown by the R-Squre value of 0,4706 where as the rest 52.94% are affected by factors outside of this research model.